The impact of Eastern enlargement on EU-labour markets / Pensions reform between economic and political problems - Herbert Brücker; Florence Legros (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Contents: 1 - Jürgen von Hagen, Jean Pisani-Ferry - Forum Economique Franco-Allemand /Deutsch-Französisches Wirtschaftspolitisches Forum – 4 - Herbert Brücker - The Impact of Eastern Enlargement on EU-Labour Markets – 23 - Florence Legros - Pensions Reform between Economic and Political Problems
Keywords: 330